The Learning and Differentiation Shapes and Textures of Objects by Nectar Bat Party (Phyllostomidae: Anoura) (Revista Científica Ciencias Naturales y Ambientales, 2010)
The Mirador project is a porphyry copper deposit , low to intermediate sulphidation , located on the western flank of the Cordillera del Condor, parish Tundayme , The Pangui canton in the province of Zamora Chinchipe , approximately 8km in a straight line the border with Peru , in the southeast of the country. It also made use of data collection techniques as structural faults and other discontinuities fractruras with those obtained angular measurements of the veinlets , with user-friendly tools , just as specific programs were used for handling and processing for information and structural graphics generation . The show directions and inclinations veinlets arranged so varied, yet have different preferences paragenesis course between events associated with regional tectonic controls influenced during their emplacement structures , after an analysis and synthesis were obtained ( 5 ) preferential five trends where three (3 ) of these have been associated with regional structural controls that cross the Zamora , these senses are given in N - S , E - W and NE - SW , and trends in NW direction - ESE and NNW - SSE.
Keywords: Associative learning; Law of effect; hidden object; Concept forms curiosity